Psychometric properties of the French-Canadian version of the Dark Triad Dirty Dozen. (1st December 2017) - Savard, Claudia; Simard, Caroline; Jonason, Peter K.
Abstract: The Dark Triad is a term used to describe a constellation of undesirable personality traits (i.e., Machiavellianism, narcissism, and psychopathy) that have received considerable empirical attention during the past decade. The Dark Triad Dirty Dozen (DTDD) is a concise instrument developed to assess these traits which has shown good psychometric properties. The aim of this study (N = 394) was to translate and validate a French-Canadian adaptation of the Dirty Dozen (DTDD-FC). The DTDD-FC presented (1) good internal consistency and item properties; (2) a bifactor structure (i.e. items loading on each of their respective trait factor as well as with a global factor); (3) conclusive associations with nomological network surrounding each trait (i.e., convergent and discriminant validity coefficients) and social desirability; and (4) sex differences for psychopathy. Overall, the French-Canadian adaptation of the Dirty Dozen seems to be a valid and psychometrically sound measure of the Dark Triad traits, and is comparable to the original English version. Highlights: The French-Canadian version of the Dirty Dozen shows good internal consistency. The bifactor structure provides evidence for the best model-data fit. Items discriminate well along different endorsement levels. Results support the convergent and discriminant validity of the instrument. Sex difference exists only for the psychopathy scale.